Food Safety Laws and Implementation Procedures of Pakistan and the International Health Regulations 2005 - Atifa Awan; Sayyeda Fatima (ASIAN Journal of International Peace & Security (AJIPS), 2023)
The article systematically investigates and evaluates the regulatory landscape of food safety in Pakistan, focusing on the enforcement mechanisms governed by International Health Regulations 2005 and Codex Alimentarius. The research objectives encompass a critical examination of Pakistan’s adherence to these international frameworks, identification of challenges in implementation, and exploration of the consequences arising from non-compliance. To address these objectives, the study formulates specific research questions, probing into the efficacy of regulatory enforcement, budgetary constraints affecting implementation, and the lack of uniformity in food laws across provinces. Methodologically, the research relies on an analysis of the International Health Regulations 2005 and Codex Alimentarius, coupled with a comprehensive review of Pakistan’s participation in the “Joint External Evaluation Assessment.” Findings underscore critical issues, notably the significant challenge posed by budget limitations, hindering effective implementation. Moreover, the absence of uniform food laws across provinces, coupled with disparate regulatory bodies at provincial and federal levels, contributes to confusion. The article advocates for urgent harmonization of food regulations nationwide, aligning them with international standards. Such alignment not only fulfills Pakistan’s commitments under International Health Regulations 2005 but also mitigates the risk of foreign restrictions, as witnessed during the COVID-19 pandemic.